SOSIALISASI WAWASAN KESEHATAN DASAR PADA SISWA SD MELALUI PROGRAM KULIAH KERJA NYATA INTERNASIONAL (KKN UNIVERISTAS MATARAM-FUKUSHIMA MEDICAL UNIVERSITY JEPANG) DI DESA PUYUNG KABUPATEN LOMBOK TENGAH - Haqiqi, Nirwana; Qoriasmadillah, Wanda; Fitriani, Fitriani; Utami, Ni Wayan Putri; Ichfa, Muh Syach Maulad; Arrazy, Muadz; Tate, Kazuma; Shinozuka, Miho; Ikunaga, Arisa; Miyake, Masao; Hazama, Akihiro; Prasedya, Eka Sunarwidhi (Universitas Mataram, 2024)
Rapid population growth has caused Indonesia to experience various population problems. One of the problems that often occurs at this time is health problems. West Nusa Tenggara (NTB) is a province that has the highest percentage of child morbidity in Indonesia at 21.30%. Puyung Village is a village in Jonggat Sub-district that has the largest population of 13,648 people. Based on this number, Puyung Village has diverse population problems, namely health problems in children. Through socialization and education activities carried out by KKN International students, it is hoped that it will become a forum for increasing the level of knowledge about basic health and can form good relationships between the parties involved. The intended targets in this activity are elementary school students at SD-IT Yayasan GMC and SDN 1 Puyung. The subject matter provided is the introduction of the body's organ structure, the dangers of smoking, nutritional balance and clean and healthy living behavior (PHBS). The socialization and education activities regarding health insights for elementary school students in Puyung Village were classified as successful. The parameters of success in this activity can be seen and measured based on student responses to the material provided. The questions asked by students were quite diverse and the ability of students to answer questions given by students before and after the activity increased. In addition, students who take part in this program receive the material with a happy feeling because the provision of material is done in a fun way through playing and learning using learning models that have interesting shapes, colors and mechanisms. This activity was successfully carried out because the objectives were achieved well. Thus students can apply what they have learned in their lives.